نظرية الأفعال الكلامية المعرفية عند أَمَل دُنقُل -دراسة تداولية معرفية- (مستل) - شريف, نيان عثمان; علي, إسماعيل محمد (Sulaimani Journal for Humanities, 2022)
Among the pragmatic tasks is the study of language in the light of its use. Without neglecting the meaning determined by the predicate context. Cognitive pragmatic studies explore mental abilities in the process of inference and deduction or in the interpretation of sayings. And the cognitive deliberative, whose rules were established by (Sperber and Wilson), shows how mental processes and procedures during linguistic communication at both sides, : the speaker and the receiver. Therefore, this research deals with how the mental image is transferred from the speaker to the recipient, and it is concerned with the elements that have an impact on the interpretation of speech and the formation of the image that the speaker wants to send to the recipient. The poetic discourse of (Amal Dunqul) is not immune to analysis by means of cognitive theories in general and the theory of verbal acts in particular. As it contains a set of direct and indirect purposes. This is what the researcher seeks to highlight by standing on the concept of the speech act. The research also tried to show the dynamic power of the verbal act and its achievement and impact power. This is based on the principles of mental space theory and conceptual blending.